Modulation of Neuropathic Pain by Glial Regulation in the Insular Cortex of Rats - Choi, Songyeon; Kim, Kyeongmin; Kwon, Minjee; Bai, Sun Joon; Cha, Myeounghoon; Lee, Bae Hwan (Frontiers in Molecular Neuroscience, 2022)
The insular cortex (IC) is known to process pain information. However, the analgesic effects of glial inhibition in the IC has not yet been explored. The aim of this study was to investigate the pain alleviation effects after neuroglia inhibition in the IC during the early or late phase of pain development. The effects of glial inhibitors in early or late phase inhibition in neuropathic pain were quantitatively characterized in astrocytes and microglia expressions in the IC of the neuropathic pain-induced animal model. The changes of withdrawal responses in different inhibitions were compared, and the morphological changes of glial cells with purinergic receptor expressions were analyzed. Inhibition of glial cells had an analgesic effect that persisted even after drug withdrawal. Both GFAP and CD11b/c expressions were decreased after the injection of glial inhibitors. Morphological alterations of astrocytes and microglia were observed with the expression changes of purinergic receptors. These findings indicate that the inhibition of neuroglia activity in the IC alleviates chronic pain and the purinergic receptors on glial cells are closely related to chronic pain development.